Spatial analysis of Fire Characterization along with various gradients of Season, Administrative units, Vegetation, Socio economy, Topography and Future climate change: A case study of Orissa state of India - Ahmad, Firoz; Uddin, Md Meraj; Goparaju, Laxmi (Ecological Questions, 2018)
Fire events are an increasing phenomenon these days due to the climate change. It is responsible for forest degradation and habitat destruction. Changes in ecosystem processes are also noticed. The livelihood of tribal population is also threatened. Geospatial technologies along with Remotely Sensed data have enormous capability to evaluate the various diversified datasets and to examine their relationship. In this analysis, we have utilized the long term fire events at district level for the Orissa state ofIndiaand forest fire hotspots were identified. The fire pattern was analyzed with respect to the existing vegetation types, tribal population and topography to understand its association/relationship. Furthermore, it was evaluated with future climate change data for better comprehension of future forest fire scenario. The study reveals that Kandhamal, Raygada and Kalahandi district have highest fire frequency representing around 38% of the total Orissa fire events. The vegetation type “Tropical mixed deciduous and dry deciduous forests” and “Tropical lowland forests, broadleaved, evergreen, <1000m” occupy the geographical area roughly 43% whereas they retain fire percent equivalent to 70%. Approximately 70% of forest fire occurred in the area where tribal population was high to very high. The 60% of forest fire occurred where elevation was greater than500 meterswhereas 48% of fire occurred on moderate slopes. Our observation of future climate change scenario for the year 2030 reflects the increase in summer temperature and irregular rainfall pattern. Therefore, forest fire intensity will be more in future in the state of Orissa whereas it’s intensity will be more severe in few of the district such as Kandhamal, Raygada, Kalahandi and Koraput which have significantly high forest fire events in present scenario. The outcomes of the present study would certainly guide the policymakers to prepare more effective plan to protect the forest which is main source of livelihood to the tribal population keeping in mind of future climate change impact for prioritization of various districts of state of Orissa suffering from forest fires.